Fireworks-related injury surveillance in the Philippines: trends in 2010–2014 - John Bobbie Roca; Vikki Carr de los Reyes; Sheryl Racelis; Imelda Deveraturda; Ma Nemia Sucaldito; Enrique Tayag; Michael O’Reilly (Western Pacific Surveillance and Response, 2015)
Analysis of the annual fireworks-related injury surveillance data collected by the Philippines Department of Health (DOH) in 2010–2014 was conducted to describe the profile of such injuries in the Philippines.